Religious Worldview - Ruzaliev Bekhzodjon Avazjonovich (Periodica Journal, 2022)
There is no doubt that it will serve the spiritual-educational and religious-moral growth of our people, especially our youth, in the implementation of the goals set before us in the conditions of the new Uzbekistan and at the stage of innovative development of the national development. Correct interpretation of the issues of religious consciousness and religious activity in the social environment (the general population, especially the youth) and, most importantly, is of great importance in forming a healthy belief in them. It is important not to forget that the religious worldview sets the main goal of finding logical answers to questions such as why life is given, what is the purpose of coming into the world, and what should be done to live a meaningful life
Keywords: National; Religious; worldview; Enlightenment